Influence of vegetable protein isolates on structural and mechanical properties of wheat dough - Makhynko, Valeriy; Chernish, Lyudmila; Berezhna, Oksana (My University, 2016)
The influence of soya’s, pea’s and rice’s isolates on the structural and mechanical properties of wheat dough. Dough’s’ farinogram are explored with the addition of 20% of the isolates showed that all samples bind more water than the control: the least – with the addition of rice protein isolate (5% more over the control), the most - soya’s isolate (32% more over the control). We calculated that the addition of 1 g of isolate of soya requires in additional 2.2 g of water, 1 g of protein isolate of peas – 1.4 g of water and 1 g of rice protein isolate – 1.2 g of water.
Keywords: dough; vegetable protein; isolates; dry wheat gluten; farinogram; тісто; рослинний білок; ізоляти; суха пшенична клейковина; фаринограма; тесто; растительный белок; изоляты; сухая пшеничная клейковина; фаринограмма; кафедра технології хлібопекарських і кондитерських виробів